INFORMATION ASYMMETRY, MARKET REACTION AND COMPANY PERFORMANCE: PRE AND DURING THE COVID-19 PANDEMIC - Antonius Herusetya; Sintya Andrey Lawu (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
This study examines the effect of information asymmetry and market reaction on company performance before and during the Covid-19 pandemic. The population in this study are all listed companies on the Indonesia Stock Exchange except for the financial sector with the 2018-2020 observation year. We define the observation period as pre- pandemic (2018-2019) and during the pandemic Covid-19 (2020). This study used the purposive sample selection method and obtained 953 observations. Using multiple linear regression analysis models, our study finds evidence that information asymmetry negatively affects firm performance. During the Covid-19 pandemic, this study finds weak evidence of the moderating role of Covid-19 on the relationship between information asymmetry and performance. Furthermore, this study found no evidence that the company's performance gave a market reaction, measured by the earnings response coefficient, but in the Covid-19 pandemic period, the company's performance gave a positive market reaction.